Hånd i hånd i barnehagelærerutdanningen - Alfarnes, Natalia; Anette Angeltveit, Nina; Eikefet Berland, Jannice; Egeland, Ole-Vinjar; Eikhaug, Runar; Flaa, Anne-Lise; Eltarvåg Gjesdal, Beate; Holovchuk, Svitlana; Birkeland Irgens, Tale; Hageberg Kjeka, Sæbjørg; Kvandal, Kari; Landro, Torgeir; et al. (Fagbokforlaget Vigmostad & Bjørke, 2026)
Hand in Hand in Kindergarten Teacher Education—Where Play, Subject Knowledge and Practice Meet offers a collection of research articles highlighting how theory and practice go hand in hand in all work related to children, kindergarten, and kindergarten teacher education. Here you can read, among other things, about the possibilities of play, risky play, church walks, the use of digital tools, guidance as a method, practicum in education, the kindergarten teacher as a street-level bureaucrat, and partnerships between higher education institutions and kindergartens. This anthology can be read as a whole or chapter by chapter, as each chapter can provide valuable knowledge and spark reflection on its specific topic. The book’s editors are Astrid Øien Halsnes, Associate Professor in pedagogy, and Lill Krestin Ryland, Lecturer in pedagogy. Both teach in the kindergarten teacher education program at NLA University College. Halsnes has served as program leader for several years, leads the research group Children, Kindergarten and Kindergarten Teacher Education, and contributes a chapter to the book. Ryland is currently acting program leader and contributes two chapters. The other contributors are: Natalia Alfarnes, Nina Anette Angeltveit, Jannice Eikefet Berland, Ole-Vinjar Egeland, Runar Eikhaug, Anne-Lise Flaa, Beate Gjesdal, Svitlana Holovchuk, Tale Birkeland Irgens, Sæbjørg Hageberg Kjeka, Kari Kvandal, Torgeir Landro, Wenche Langeland, Marit Myklebust, Lene Jaer Nottveit and Hilde Kartveit Sundnes. The anthology Hand in Hand in Kindergarten Teacher Education—Where Play, Subject Knowledge and Practice Meet is published in 2024 as a contribution to the 25th anniversary of the kindergarten teacher education program at NLA University College.